Shanling Jiangzhi Tea treats hyperuricemia by inhibition of COMT/MAOA signaling pathway and p53/SERPINE1/NLRP3 signaling pathway - Chen, Hao-nan; Wu, He-zhen; Yang, Yan-fang (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the therapeutic efficacy of Shanling Jiangzhi Tea (SLJZ) on hyperuricemia (HUA) mice and to investigate its mechanism.MethodsA HUA mouse model was established using a combination of uric acid (UA)and potassium oxonate. Following SLJZ intervention, changes in body weight were monitored. Renal lesions and renal fibrosis were assessed via H&E staining and Masson trichrome staining. Serum levels of UA, creatinine (Cr), blood urea nitrogen (BUN), and xanthine oxidase (XOD) were measured to evaluate the UA-lowering effects of SLJZ. Ultra-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was employed to identify the bioactive components of SLJZ that entered the bloodstream. Network pharmacology, molecular docking, and transcriptomics analyses were conducted to elucidate the key targets and signaling pathways involved in SLJZ’s therapeutic effects on HUA. Protein expression levels were further validated using immunohistochemistry.ResultsSLJZ significantly reduces the levels of UA, Cr, BUN, and XOD in the blood of HUA mice, alleviates inflammatory cell infiltration, attenuates renal interstitial fibrosis, and demonstrates therapeutic potential for hyperuricemia. RNA-seq analysis reveals that SLJZ reverses 280 HUA-induced differentially expressed genes (DEGs) in the kidneys. Based on the findings from network pharmacology and molecular docking analyses, SERPINE1, p53, NLRP3, COMT, and MAOA are identified as potential key proteins involved in SLJZ’s treatment of HUA. Kit-based assays indicate that SLJZ increases dopamine (DA) levels in the kidneys of mice while reducing the levels of interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). Immunohistochemical results confirm that SERPINE1, p53, NLRP3, COMT, and MAOA are significantly upregulated in the kidneys of HUA model mice, but their expression is normalized following SLJZ intervention.ConclusionSLJZ exhibits a significant anti-HUA effect by inhibiting the COMT/MAOA signaling pathway and the p53/SERPINE1/NLRP3 signaling pathway. Through these mechanisms, SLJZ is involved in the DA metabolic process, modulates the inflammatory response mediated by the SERPINE1 fibrinolytic system, alleviates renal tubulointerstitial fibrosis, and mitigates oxidative stress, thereby exerting therapeutic effects on HUA.